Efeito da administração crônica do salbutamol sobre alterações comportamentais e neuroquímicas de um modelo experimental de parkinsonismo - Carvalho, Milena Caroline Nunes Monteiro de (2023)
Parkinson's disease (PD) is characterized by the death of dopaminergic neurons in the nigrostriatal pathway, however, dysfunction of other neuronal pathways is also associated with its progression. In this regard, studies have supported the idea that the use of adrenergic-β2 agonist drugs may decrease the risk for developing the disease. The present study evaluated the effect of chronic administration of salbutamol (an adrenergic-β2 agonist) on motor and behavioral changes in an experimental model of reserpine-induced parkinsonism. We used 45 Wistar rats, aged 4 to 6 months, divided into 4 groups: control (n=9), salbutamol (n=10), reserpine (n=12) and reserpine-salbutamol (n=14), treated with salbutamol 5 mg/kg or vehicle, s.c., daily for 75 days. After 45 days of salbutamol treatment, the animals were induced to parkinsonism by 15 injections of reserpine 0.1 mg/kg, s. c, one every 48h, until day 75 and subjected to the behavioral tests of catalepsy, oral movements (MO), open field (AC) and spontaneous alternation (AE), and 48 hours after the last reserpine injection the animals were anesthetized and perfused for collection of the encephalons, which were subsequently processed and subjected to immunohistochemistry for tyrosine hydroxylase (TH) and α-synuclein (α-sin). CEPA, no. 4200070621. After the analysis of behavioral data, it was observed that in the catalepsy test, the RES group showed higher latency compared to the CTR, from day 12 to 30 (p<0.05); on the other hand, the RES-SALB group showed lower latency compared to the RES group, from day 16 to 30 (p<0.05) and higher latency compared to the SALB group, from day 14 to 30 (p<0.05). In the MO test, the RES and RES-SALB groups had higher vacuum chewing, tongue protrusion, and longer oral tremor time on days 18 and 30 compared to the CTR and SALB, respectively, (p<0.05). In the AC test, the RES-SALB group had longer dwell time in the center of the apparatus compared to the other groups CTR, SALB and RES (p<0.05). In the AE test, the RES and RES-SALB groups had fewer correct alternations compared to the CTR group (p<0.05). The SALB group had a significant increase in mass compared to the CTR group, while the RES and RES-SALB groups had a significant decrease in mass compared to CTR and SALB (p<0.05), respectively. In addition, the RES-SALB group showed greater mass loss compared to the RES group (p<0.05). Regarding immunoreactivity, it was observed that salbutamol prevented against the reduction of cells immunoreactive for TH, in the substantia nigra part compacta (SNpc), dorsal striatum and ventral tegumentary area (VTA), comparing the RES group to the RES-SALB group (p<0.05). However, for α-sin accumulation, salbutamol was not preventive, the RES and RES-SALB groups showed a higher density, in the reticular substantia nigra (SNr), striatum and medial prefrontal cortex (CPFm), compared to the CTR group (p<0.05). Our results suggest that chronic salbutamol treatment can attenuate motor deficit in catalepsy and prevent TH depletion, but not against reserpine-induced increase in αsin. However, further studies are needed to clarify the relationship between the attenuating effect of chronic salbutamol treatment and the motor and neurochemical damage associated with the progressive reserpine-induced parkinsonism model.